2023
DOI: 10.1039/d2sc06445f
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling upsurge of photogenerated ROS: control of intersystem crossing through tuning aggregation patterns

Abstract: The influence of aggregation patterns on intersystem crossing (ISC) was investigated by constructing homologous monomers (S-TPA-PI and L-TPA-PI) and their homologous dimers (S-2TPA-2PI and L-2TPA-2PI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Conjugated organic molecules with suitable energy levels can generate reactive oxygen species (ROS) under light irradiation, which find widespread applications in fields such as photocatalysis and photodynamic therapy. The aggregation and aggregation mode can significantly affect the release of ROS. , Our research has revealed the influence of aggregate structures on the generation of ROS, highlighting the pronounced enhancement of ROS production facilitated by “end-to-end” stacking interactions. , In photovoltaic devices, the acceptor predominantly adopts an “end-to-end” stacking pattern, suggesting the potential generation of ROS by the acceptor itself under light irradiation. , However, to the best of our knowledge, there is currently a lack of relevant research. In order to provide deeper insights into this matter, leveraging the advantageous features of our previously developed nonfused-ring electron acceptors with expedited molecular construction, we employed reported LC8 and BC8 as model systems .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Conjugated organic molecules with suitable energy levels can generate reactive oxygen species (ROS) under light irradiation, which find widespread applications in fields such as photocatalysis and photodynamic therapy. The aggregation and aggregation mode can significantly affect the release of ROS. , Our research has revealed the influence of aggregate structures on the generation of ROS, highlighting the pronounced enhancement of ROS production facilitated by “end-to-end” stacking interactions. , In photovoltaic devices, the acceptor predominantly adopts an “end-to-end” stacking pattern, suggesting the potential generation of ROS by the acceptor itself under light irradiation. , However, to the best of our knowledge, there is currently a lack of relevant research. In order to provide deeper insights into this matter, leveraging the advantageous features of our previously developed nonfused-ring electron acceptors with expedited molecular construction, we employed reported LC8 and BC8 as model systems .…”
Section: Introductionmentioning
confidence: 84%
“…25,26 Our research has revealed the influence of aggregate structures on the generation of ROS, highlighting the pronounced enhancement of ROS production facilitated by "end-to-end" stacking interactions. 27,28 In photovoltaic devices, the acceptor predominantly adopts an "end-to-end" stacking pattern, suggesting the potential generation of ROS by the acceptor itself under light irradiation. 21,29−31 However, to the best of our knowledge, there is currently a lack of relevant research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As the key component of PDT, designing a powerful and effective PS with tremendous ROS generation in a tumor area is of crucial importance. Since the report of hematoporphyrin derivatives (HpDs) as PSs in 1960, various types of PSs including Chlorin Ce6, methylene blue, indocyanine green, and BODIPY derivatives have been developed. However, their antitumor performance is greatly compromised due to their reduced ROS generation in aggregates (being encapsulated into nanoparticles or enriched in specific tumor area) and the hypoxia tumor microenvironment. Therefore, developing PSs with less oxygen dependence and uncompromised ROS in aggregates is in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained PSs were characterized by 1 H NMR, 13 C NMR, and ESI-MS (Figures S1–S20). The single crystals of TPA-OTs and TPA-BPh 4 were measured by X-ray diffraction and analyzed crystal lographically, and the specific crystal data are summarized in Tables S1 and S2.…”
mentioning
confidence: 99%